Disclosure of intellectual capital in mediterranean countries - Martins, Maria Manuela (2022)
This article presents the results of an investigation into the state of research in intellectual capital in the Mediterranean context through the analysis of 15 studies published in journals. The purpose of this study is to conduct a survey of papers on disclosure of intellectual capital information in Mediterranean countries. The results show the majority of studies on disclosure of intellectual capital in Mediterranean countries are made in European countries. France, Greece, Italy, Jordan, Portugal and Spain were the only ones of the 26 Mediterranean countries to examine the disclosure of intellectual capital, and the two countries of the Iberian Peninsula are responsible for ten of these papers..